Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T19:31:33+01:00
{x-y=0
{x+y+z=4
{x+2y+3z=9

Z pierwszegp r-nia
x=y wstawiamy do drugiego i trzeciego

{x=y
{x+x+z=4
{x+2x+3z=9

{x=y
{2x+z=4
{3x+3z=9/:3

{x=y
{z=4-2x wstawiamy do 3-go
{x+4-2x=3 czyli

-x=3-4
-x=-1/:(-1)
x=1
y=1
z=4-2*1=2

Rozwiązaniem r-nia są liczby (1,1,2)


1 1 1
  • 55a
  • Początkujący
2009-12-06T19:32:55+01:00
X-y=0
x+y+z=4
x+2y+3z=9

x=y
x+x+z=4
x+2*x+3z=9

x=y
2x+z=4
3x+3z=9

x=y
z=4-2x
3x+3(4-2x)=9

x=y
z=4-2x
3x+12-6x=9

x=y
z=4-2x
-3x=9-12 -3x=-3 x=1

x=y
z=4-2*1 z=4-2=2
x=1

x=1 y=1 z=2